Stability and transformation in gender, work, and family: Insights from the second shift for the next quarter century - Blair-Loy, Mary; Hochschild, Arlie; Pugh, Allison J.; Williams, Joan C.; Hartmann, Heidi (Community, Work and Family, 2015)
Arlie Hochschild's The second shift: Working families and the revolution at home argued that the revolution toward gender equality in the USA has been stalled due to three factors: (1) women continue to do most of the ‘second shift’ – the unpaid work of childcare and housework; (2) insufficient flexibility in the workplace for accommodating family caregiving needs; and (3) a deficit of public sector benefits, such as paid parental leave. Since the book's publication in1989, many aspects of the gender structure (how gendered opportunities, barriers, and cultural meanings are socially structured in the USA) remain the same. Yet many aspects have changed. This article looks at areas of stability in the gender structure and areas of transformation in the past quarter century. We then plumb the book for the analytical insights it generates for scholars today. We discuss how deep-seated cultural understandings of gender infuse all levels of analysis: macro-level policies, family and work institutions, and personal experiences of gender, intimacy, and moral commitments. These insights help illuminate paths forward for new research on how new economic developments, including economic insecurity, flexibilization (the increasingly reliance on temporary and contract labor), and the widening social class divide, continue to affect intimacy at home. © 2015 Taylor & Francis.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; discipline; double journée de travail; histoire et politique; inégalités hommes-femmes; maternité; projet charge mentale; périodes historiques; régions géographiques; sciences humaines; sociologie; soins aux enfants; thématiques; travail; travail domestique; états-unis

Le care : éthique féministe actuelle - Bourgault, Sophie; Perreault, Julie (Les éditions du remue-ménage, 2015)
Cet ouvrage présente une réflexion pluridisciplinaire sur l'éthique féministe du care. Élaborée par Carol Gilligan dans In a Different Voice en 1982, cette «éthique de la sollicitude» a été très prisée dans les années 1980. Plus récemment, nous assistons à l'émergence d'une enthousiaste seconde génération de théoricien.ne.s du care qui y voient un terreau fertile pour réfléchir aux oppressions liées à la division genrée du travail.Comment ce renouveau se traduit-il? Quels sont les enjeux éthiques, politiques et épistémologiques que permet de mettre en lumière cette approche? Le care équivaut-il essentiellement au travail de soin effectué en majorité par les femmes, ou comprend-il l'ensemble des services domestiques, affectifs et sexuels fournis dans un rapport d'interdépendance?L'originalité de ce premier ouvrage faisant le point sur la question au Québec tient entre autres à son souci constant de débarrasser le care du sentimentalisme qu'on lui a souvent reproché, et surtout, de le réinvestir de tout son potentiel critique et féministe.Avec des textes de Bettina Bergo, Agnès Berthelot-Raffard, Sophie Bourgault, Sophie Cloutier, Marjolaine Deschênes, Stéphanie Gaudet, Naïma Hamrouni, Mariko Konishi, Monique Lanoix, Patricia Paperman et Julie Perreault.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; care; discours dominant; division sexuelle du travail; inégalités; patriarcat; projet charge mentale; périodes historiques; québec; ressource en ligne; régions géographiques; santé; santé mentale; systèmes d'oppressions; thématiques; travail

Food and femininity - Cairns, Kate; Johnston, Josée (Bloomsbury Academic, 2015)
"Over the space of a few generations, women's relationship with food has changed dramatically. Yet – despite significant advances in gender equality – food and femininity remain closely connected in the public imagination as well as the emotional lives of women. While women encounter food-related pressures and pleasures as individuals, the social challenge to perform food femininities remains: as the nurturing mother, the talented home cook, the conscientious consumer, the svelte and health-savvy eater. In Food and Femininity, Kate Cairns and Josée Johnston explore these complex and often emotionally-charged tensions to demonstrate that food is essential to the understanding of femininity today. Drawing on extensive qualitative research in Toronto, they present the voices of over 100 food-oriented men and women from a range of race and class backgrounds. Their research reveals gendered expectations to purchase, prepare, and enjoy food within the context of time crunches, budget restrictions, political commitments, and the pressure to manage health and body weight. The book analyses how women navigate multiple aspects of foodwork for themselves and others, from planning meals, grocery shopping, and feeding children, to navigating conflicting preferences, nutritional and ethical advice, and the often-inequitable division of household labour. What emerges is a world in which women's choices continue to be closely scrutinized – a world where 'failing' at food is still perceived as a failure of femininity. A compelling rethink of contemporary femininity, this is an indispensable read for anyone interested in the sociology of food, gender studies and consumer culture."
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; care; corps; corps féminin; cours; discipline; inégalités; ontario; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; sexisme; soc2264; sociologie; systèmes d'oppressions; thématiques; toronto; travail

Les mesures d'austérité et les femmes: analyse des documents budgétaires depuis novembre 2008 - Couturier, Eve-Lyne; Tremblay-Pépin, Simon; Institut de recherche et informations socio-économiques (IRIS, 2015)
Contrairement à ce que défend le gouvernement du Québec, celui-ci mène actuellement des politiques d'austérité. Ces politiques ont croisé un certain nombre de mesures de relance que le Québec a tenté d'établir depuis la crise de 2008, mais il n'en demeure pas moins que les compressions ont été plus importantes que les investissements. Cette étude montre que si les mesures de relance ont d'abord favorisé les hommes, les mesures d'austérité, quant à elles, ont surtout affecté les femmes. Ces dernières se trouvent donc doublement perdantes vis-à-vis des mesures instaurées par le gouvernement québécois depuis la crise. Si elle diffère en termes de degré, cette situation correspond à celle qu'on a pu observer en Europe lors de la mise en place de mesures d'austérité.
disponible gratuitement à https://iris-recherche.qc.ca/wp-content/uploads/2021/03/Femmes_et_austerite_WEB.pdf
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; austérité; canada; capitalisme; cours; discipline; histoire et politique; inégalités; patriarcat; pol4102; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; sexisme; sofia; systèmes d'oppressions; thématiques; travail; violences

The mask you live in (Kanopy Streaming, 2015)
HE MASK YOU LIVE IN follows boys and young men as they struggle to stay true to themselves while negotiating America’s narrow definition of masculinity. Pressured by the media, their peer group, and even the adults in their lives, our protagonists confront messages encouraging them to disconnect from their emotions, devalue authentic friendships, objectify and degrade women, and resolve conflicts through violence. These gender stereotypes interconnect with race, class, and circumstance, creating a maze of identity issues boys and young men must navigate to become “real” men. Experts in neuroscience, psychology, sociology, sports, education, and media also weigh in, offering empirical evidence of the “boy crisis” and tactics to combat it. The Mask You Live In ultimately illustrates how we, as a society, can raise a healthier generation of boys and young men.
Place: San Francisco, California, USA
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; care; cinéma; communication; cours; discipline; documentaire; féminisme pop; histoire et politique; intersectionnalité; masculinité; premier cycle; périodes historiques; représentation des hommes; régions géographiques; sex2283; sexualité; thématiques; travail; violences; états-unis